If i apply the DTFT on unit step function, then i get follow: $$DTFT\{u[n]\}=\sum_{n=-\infty}^{\infty}u[n]e^{-j\omega n}=\sum_{n=0}^{\infty}e^{-j\omega n} = \frac{1}{1-e^{-j\omega}}$$.

Now i have the problem, if $|e^{-j\omega}|$ = 1, the sum diverges.To handle this case, i know that $e^{-j\omega}$ is $2\pi$ periodic, i get $$\frac{1}{1-e^{-j\omega}}+\underbrace{e^{-j0}}_1 \sum_{k=-\infty}^{\infty}\delta(\omega+2\pi k)$$.

In books i found that the DTFT of the unit step is $$\frac{1}{1-e^{-j\omega}}+\pi \sum_{k=-\infty}^{\infty}\delta(\omega+2\pi k)$$.

Can me anyone explain why get the $\pi$ in the DTFT of the unit step?

  • $\begingroup$ that the sum diverges is a problem, that's why there is the Fourier inversion theorem, the extension of the Fourier transform to $L^p$ functions and then to distributions in term of bounded operators of Banach space, etc. and I don't get what you did. so you can compute the Fourier series of $\frac{1}{1-e^{- i \omega}}$ and check that the coefficients are $u[n]-1/2$. or you can consider the DTFT of $\frac{u[n-1]}{n}$ and prove that it is $-\ln(1-e^{-i \omega})$ with the Taylor series of $-\ln(1-z)$ at $z=0$ (and $(-\ln(1-z))' = \frac{1}{1-z}$) $\endgroup$ – reuns May 5 '16 at 5:53

Hi guys I think this way is better than others,What's Ur idea?

$u[n]=f[n] + g[n] $


$f[n]= {1\over2}$ for $-\infty<n<\infty $


$g[n]=\left\{ \begin{array}{c} {1\over2} \text{ for } n\ge 0 \\ {-1\over2} \text{ for } n<0 \end{array} \right.$


$ \delta [n] = g[n] - g[n-1]$

U Know DTFT of $\delta[n]$ is $1$ and DTFT of $g[n] - g[n-1]\to G(e^{j\omega})-e^{-j\omega}G(e^{j\omega})$ so: $1=G(e^{j\omega})-e^{-j\omega}G(e^{j\omega})$


$G(e^{j\omega})={1\over 1-e^{-j\omega}}$

and we know that the DTFT of $f[n]\to F(e^{j\omega})=\pi\sum_{k=-\infty}^\infty\delta(\omega -2\pi k)$

finally :

$u[n] = f[n]+g[n] \to U(e^{j\omega})=F(e^{j\omega})+G(e^{j\omega})$

$U(e^{j\omega})={1\over 1-e^{-j\omega}}+\pi\sum_{k=-\infty}^\infty\delta(\omega -2\pi k)$


Firstly, you need to be aware that

$$u[n]=\sum_{n=0}^{\infty} \delta[n]$$

And according to Accumulation property of DTFT which implies that: $$y[n]=\sum_{m=-\infty}^{n}x[m]$$ $$\sum_{m=-\infty}^{n}x[m]{\iff}\frac{1}{1-e^{-j\omega}}X(e^{j\omega}) + \pi X(e^{j0})\sum_{k=-\infty}^{\infty}\delta(\omega - 2\pi k)\ \ \ \ *$$ Now assume that: $$x[n] =\sum_{m=-\infty}^{n} g[m]$$ $$g[n] =\delta[n]$$ $$G({e^{j\omega}}) = 1$$

Substitute in *: $$\frac{1}{1-e^{-j\omega}}G(e^{j\omega}) + \pi G(e^{j0})\sum_{k=-\infty}^{\infty}\delta(\omega - 2\pi k)$$ Now refine the last formula:

HINT: $G(e^{j\omega}) = 1\\ G(e^{j0}) = 1$ $$\frac{1}{1-e^{-j\omega}} + \pi \sum_{k=-\infty}^{\infty}\delta(\omega - 2\pi k)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.